If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + -6m = 40 Combine like terms: 2m + -6m = -4m -4m = 40 Solving -4m = 40 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '-4'. m = -10 Simplifying m = -10
| 8x+3y=-28 | | -4w=4-7 | | 6h=36 | | -8/11-(7/8)= | | an=3+.3(n-1) | | -4w=4-7w | | -8/11-7/8= | | .65x+4.99=6.94 | | (8-5i)/i | | h+7-4h=(-8) | | 2x-5(42)=-10 | | 7-2a=3a | | -7/9k=1/18-7/18 | | 0.6(3x-17)=(32-4x) | | (3x+5)*8=a | | -2x-6(42)=32 | | r+6=45 | | 4w-5=43 | | 7v-5=4-2v | | -5+7-4(-5)=(-8) | | 3y-11.5=-48.5 | | 5d-6+6=24 | | A^2+b^2-c^2=0 | | -5f+28=-21 | | a=1/x-1/y | | 4z+3=19-4z | | 3x+5+2x=2x+20 | | 6x+3(-2x+4)=8 | | (6-4)180=360 | | 2(x+4)=6r | | 2n^2=7-2n | | 80=4x-40 |